Distinctive Feature Analysis of Kannada Consonants - Venkatesh CS (Journal of All India Institute of Speech and Hearing, 1970)
The language has several levels, like Semantic, Syntactic, Morphemic and Phonemic levels. The Phonemic level is the lowest and most fundamental level. Complex  objects and events have sub-units or recognizable properties. These properties are termed  as features. The features which help to distinguish between two entities are called as distinctive features. The present study is an attempt to analyze the distinctive features of Kannada consonants.